The main categories of NewSQL databases and their features - Yesin, V.I.; Vilihura, V.V. (Radiotekhnika, 2022)
In the modern world, the problem of working with big data and workloads is becoming more and more acute. For more than forty years, relational databases have been the main leading systems for storing, searching and managing data. However, despite their great popularity, application experience and universality, traditional relational DBMS, due to the growing needs for scalability and performance, often cannot meet modern requirements. This has led to the emergence of new alternative data management systems, including NewSQL systems. NewSQL is a class of modern relational database management systems that provide performance comparable to NoSQL systems while maintaining the data consistency guarantees inherent in traditional database systems. The growing interest in NewSQL technology in recent times has led to an increase number of evaluations and comparisons among competing NewSQL technologies. However, today there is still a certain lack of work devoted to the study of the features of NewSQL solutions and their capabilities in comparison with other technologies. This paper discusses the main features of the most famous NewSQL products of different categories and the identified problems associated with them. To overcome the certain ambiguity in the names and translations of some terms related to the subject area under consideration, which takes place in numerous relevant sources, additional explanations are given. For comparison, the paper presents the values of important characteristics inherent in NewSQL, traditional relational and NoSQL database systems. This paper can help researchers and people from the industry choose the best storage solutions for their needs.